Legally yours - Iyer, V. R. Krishna (New Delhi, 2013)
The Constitution of India operates through in happy harmony with the instrumentalities of the Executive and the Legislature. But the Judiciary exercising democratic power to be truly great must enjoy independence of a high order. But independence became dangerous and undemocratic unless there is a constitutional discipline with rules of good conduct and accountability sans which the robes may prove arrogant. It is in this context Chief Justice Kapadia's recent observations have to be reconciled with what the Law Minister Salman Khurshid has observed about judicial propriety. It is this reconciliation of the trinity of instrumentality in their functionalism that does justice to the Constitution at work. A great and grand chapter on judicial sublime behaviour to forbid the 'robes' becoming unruly or rude but ever sober is obligatory. A la! the recent conflict of Ipse Dixit between Chief Justice S.H. Kapadia and Law Minister Salman Khurshid.
Keywords: "Iyer, V.R. Krishna-Collection of legal writings"